1985
DOI: 10.1002/jcp.1041240205
|View full text |Cite
|
Sign up to set email alerts
|

Production of insulin‐like growth factor‐II (MSA) by endoderm‐like cells derived from embryonal carcinoma cells: Possible mediator of embryonic cell growth

Abstract: The present study was carried out to determine if an insulin-like growth factor (IGF) type activity might be produced by embryonal carcinoma-derived cells. The cell line used to condition growth medium for the isolation of secreted growth factors was a newly established Dif 5 cell type. Dif 5 cells are a differentiated endoderm-like cell type derived from F9 embryonal carcinoma cells (which possess properties similar to mouse embryonic stem cells) following extensive exposure to retinoic acid. When growth medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

1988
1988
1994
1994

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 33 publications
(30 reference statements)
1
5
0
1
Order By: Relevance
“…There are several reports on the role of growth factors in these processes (for a recent review see [23]). Production of insulin-like growth factors (IGFs) is a general observation for differen-* To whom offprint requests should be sent tiated EC cells, but reduced levels of production have also been observed in the undifferentiated stem cells [32,411. Gudas et al [I71 and Rizzino and Bowen-Pope [37] reported the production of a platelet-derived growth factor-like (PDGF-like) protein by PSA-IG, F9, and PC13 EC cells.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on the role of growth factors in these processes (for a recent review see [23]). Production of insulin-like growth factors (IGFs) is a general observation for differen-* To whom offprint requests should be sent tiated EC cells, but reduced levels of production have also been observed in the undifferentiated stem cells [32,411. Gudas et al [I71 and Rizzino and Bowen-Pope [37] reported the production of a platelet-derived growth factor-like (PDGF-like) protein by PSA-IG, F9, and PC13 EC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Human and mouse teratocarcinoma cell lines produce IGF-I and the type I IGF receptor (15,(18)(19)(20). Teratocarcinoma consists of malignant undifferentiated embryonic carcinoma (EC) cells and various somatic tissue intermingled (21,22).…”
mentioning
confidence: 99%
“…Isacke and Deller (1983) and Rizzino et al (1983) have reported that coculture of undifferentiated embryonal carcinoma cells with established fibroblast cells supported the growth of the fibroblasts, apparently owing to growth factors secreted into the culture medium by the stem cells. Recently, Heath and Isacke (1984) reported the isolation of a growth factor from medium conditioned by PC 13 embryonal carcinoma stem cells, and we have shown that Dif 5 endoderm and visceral endoderm-like PSA6E cells secrete significant amounts of IGF-I1 (Nagarajan et al, 1985). Gudas et al (1983) and Rizzino and Bowen-Pope (1985) have reported that undifferentiated teratocarcinoma stem cells secrete a PDGF-related growth factor.…”
Section: Discussionmentioning
confidence: 95%